已知f(x)=2x,则f(-2)=
A: -1
B: 2
C: -4
D: 1
A: -1
B: 2
C: -4
D: 1
C
举一反三
- 已知函数f(x)是线性函数,且f(-1)=2 ,f(1)=-2 ,则f(x)=() A: x+3 B: x-3 C: 2x D: -2x E: 3x
- 已知f(2x)=2^x,则f(x)=
- 已知f(x)= ax+b,且f(-1)=2,f(1)=-2,则f(x)=( )
- 已知 \(f(1) = 1,f(2) = 3\),那么 \(y = f(x)\) 以\(x = 1,2\) 为节点的lagrange线性插值多项式为 A: \({L_1}(x) = 2x + 1\) B: \({L_1}(x) = 2x - 1\) C: \({L_1}(x) = 2x - 3\) D: \({L_1}(x) = 2x - 4\)
- 已知$f(x),\ g(x)$互为反函数,且$f(1)=2,\ {g}'(2)=2,\ {g}''(2)=1$,则${f}''(1)=$( )。 A: $1$ B: $\frac{1}{2}$ C: $-\frac{1}{4}$ D: $-\frac{1}{8}$
内容
- 0
f(x)=x2+bx+c,x∈R,有f(2+x)=f(2-x),则( ) A: f(1)<f(2)<f(4) B: f(2)<f(4)<f(1) C: f(4)<f(2)<f(1) D: f(2)<f(1)<f(4) E: f(1)<f(4)<f(2)
- 1
已知f(x)在R上是奇函数,且f(x+4)=f(x),f(1)=2,则f(7)=( ) A: -2 B: 2 C: -4 D: 4
- 2
已知函数f(x)=2x-1,则f(2)= A: 1 B: 2 C: 3 D: 4
- 3
F(x1,x2,x3)= x 1 2 +2x 2 2 +5x 3 2 +2x 1 x 2 +2x 1 x 3 +6x 2 x 3 的标准形为()
- 4
设函数f(x)=a|x|(a>0),且f(2)=4,则( ) A: f(-1)>f(-2) B: f(1)>f(2) C: f(2)<f(-2) D: f(-3)>f(-2)